Extensive Collection of Psychotropic Mushrooms with Determination of Their Tryptamine Alkaloids - Gotvaldová, Klára; Borovička, Jan; Hájková, Kateřina; Cihlářová, Petra; Rockefeller, Alan; Kuchař, Martin (International journal of molecular sciences, 2022)
Since not only psilocybin (PSB) but also PSB-containing mushrooms are used for psychedelic therapy and microdosing, it is necessary to know their concentration variability in wild-grown mushrooms. This article aimed to determine the PSB, psilocin (PS), baeocystin (BA), norbaeocystin (NB), and aeruginascin (AE) concentrations in a large sample set of mushrooms belonging to genera previously reported to contain psychotropic tryptamines. Ultra-high performance liquid chromatography coupled with tandem mass spectrometry was used to quantify tryptamine alkaloids in the mushroom samples. Most mushroom collections were documented by fungarium specimens and/or ITS rDNA/LSU/EF1-α sequencing. Concentrations of five tryptamine alkaloids were determined in a large sample set of 226 fruiting bodies of 82 individual collections from seven mushroom genera. For many mushroom species, concentrations of BA, NB, and AE are reported for the first time. The highest PSB/PS concentrations were found in Psilocybe species, but no tryptamines were detected in the P. fuscofulva and P. fimetaria collections. The tryptamine concentrations in mushrooms are extremely variable, representing a problem for mushroom consumers due to the apparent risk of overdose. The varied cocktail of tryptamines in wild mushrooms could influence the medicinal effect compared to therapy with chemically pure PSB, posing a serious problem for data interpretation.
Keywords: Psilocybe; Agaricales; psilocin; baeocystin; tryptaminy; Alkaloids; hallucinogenic fungi; psilocybin; alkaloidy; Tryptamines